2021
DOI: 10.3390/su131810274
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Instructional Delivery Modality on Sustainability Literacy

Abstract: As human environmental impacts have increased, so has the desirability of sustainable practices in multiple dimensions and at multiple scales. In this context, sustainability literacy has become a desirable outcome of higher education, driving the advance of sustainability as a core component of higher education institutions’ missions at local, regional, and global scales. However, little is known about the efficacy of different instructional delivery modalities of higher education courses in delivering desire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Ref. [69] in this special edition examined the relationship between studying abroad and sustainable literacy. Interestingly, this included the notion that "studying non-sustainability courses abroad showed comparable growth in students' sustainability literacy scores compared to studying sustainability on home campuses" [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [69] in this special edition examined the relationship between studying abroad and sustainable literacy. Interestingly, this included the notion that "studying non-sustainability courses abroad showed comparable growth in students' sustainability literacy scores compared to studying sustainability on home campuses" [69].…”
Section: Discussionmentioning
confidence: 99%
“…[69] in this special edition examined the relationship between studying abroad and sustainable literacy. Interestingly, this included the notion that "studying non-sustainability courses abroad showed comparable growth in students' sustainability literacy scores compared to studying sustainability on home campuses" [69]. In the present study, results revealed heterogeneity in reported levels of deep learning activity as a function of the topic of the coursework students were enrolled in (i.e., sustainability versus non-sustainability) and the location where it occurred (i.e., study abroad vs. on campus).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and Gibson's (2021) study showed that graduates of study abroad offerings involving sustainability content often retained a sustainability focused mindset long after participation. Similarly, Ling et al (2021) found that sustainability courses embedded in study abroad provided the greatest gains in sustainability literacy compared to on-campus sustainability-themed courses. Among the course variables (i.e.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The contribution from Ling, Landon, Tarrant, and Rubin [3] examines the impact coursework in sustainability, taken on campus or as part of an educational travel program, has on participants' sustainability literacy (economic, environmental, and social). Using an assessment tool developed from other existing surveys, the authors found that sustainability courses embedded within an ETP provided the largest, most significant gains in sustainability literacy compared to on-campus courses (both ones that dealt with sustainability themes or other non-sustainability related courses) and other ETPs that did not deal explicitly with a sustainability-related theme.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…The contributions in this Special Issue focus on ETPs in higher education in Europe [1,2] and the United States [3][4][5][6][7]. They examine both immediate [1,[3][4][5] and longterm [7] educational gains for the students participating in ETPs in general and those that focus on sustainability or the environment. They also consider the impacts that the host community might experience from these programs [2,6].…”
Section: Introductionmentioning
confidence: 99%